Precambrian ophiolites and related rocks - Kusky, Timothy M. (Developments in Precambrian geology, 2004)
Recent developments have shown that many full and partial ophiolites are preserved in Precambrian cratons. This book provides a comprehensive description and discussion of the field aspects, geochemistry, geochronology and structure of the best of these ophiolites. It also presents syntheses of the characteristics of ophiolites of different ages, and an analysis of what the characteristics of these ophiolites mean for the thermal and chemical evolution of the earth. This title emphasizes new studies of Precambrian Geology that have documented ophiolites, ophiolitic fragments, and ophiolitic melanges in many Precambrian terranes. Each chapter focuses on individual Precambrian ophiolites or regions with numerous Precambrian ophiolites, and covers field aspects, petrology, geochemistry, geochronology, and other descriptive aspects of these ophiolites, it also delves into more theoretical and speculative aspects about the interpretation of the significance of these ancient ophiolites.